The -765G>C Cyclooxygenase-2 Promoter Polymorphism is associated with Type 2 Diabetes Mellitus, Low High-density Lipoprotein and Manifest Angina - Rachel Churm (Journal of Diabetes & Metabolism, 2016)
Background & Aims: Cycloxygenase-2 (COX-2) catalyses the rate limiting step of prostaglandin biosynthesis. Despite previous studies, it is still unclear whether COX-2 is beneficial or detrimental to cardiovascular risk. The aim of this study was to examine the -765G>C (rs20417) PTGS2 promoter gene variant, which encodes COX-2, in relation to markers of cardiovascular risk in a sample of well-characterised subjects with diabetes mellitus. Methods & Results: We observed that the CC genotype was more prevalent in Type 2 diabetes mellitus compared to Type 1 (84.2 vs 15.8%; p≤0.05), and was significantly associated with clinically manifest angina (GG vs GC vs CC: 14.3% vs 15.6% vs 28.0%; p=0.009) and lower HDL-cholesterol levels (GG vs GC vs CC: 1.3mmol/L vs 1.4mmol/L vs 1.2mmol/L; p=0.032). This is in line with previous studies showing that -765G>C genotype variant alters Sp1 binding, resulting in decreased COX-2 activity which is associated with atherosclerosis. Conclusion: We conclude that the CC genotype may contribute to a reduction of prostaglandin E2 mediated insulin secretion, predisposing those individuals to Type 2 diabetes mellitus. Further prospective work is warranted in order to examine the association between COX-2 and cardiovascular risk.